PENERAPAN ALGORITMA NAÏVE BAYES CLASSIFICATION UNTUK KLASIFIKASI SENTIMENT TWEET TERHADAP PLATFORM STREAMING ILEGAL - Wahyu, Angga Sukma; Wibowo, Jati Sasongko; Brama Arya Di Putra, I Putu (LPPM Institut Teknologi Bisnis Dan Bahasa Dian Cipta Cendikia, 2023)
According to a survey by the Coalition Against Piracy (CAP) of the Asia Video Industry Association, 63% of onlinestreaming service users in Indonesia prefer to watch illegal streaming platforms for free with various